Protecting Bank Deposits. (Economic Issues; Economic Issues ;, 1997)
Banking crises have led many countries to consider deposit insuranceschemes to protect depositors and the banking system itself from the impact of bank failures. But should society be unconditionally responsible for underwiting banking decisions, even those imprudentlytaken? This paper considers the fine line that government authorities must tread between assuring the health of the banking system and encouraging recklessness on the part of individual banks by overprotecting deposits.